Anais Do Encontro Internacional Do Processo De Enfermagem 2017
DOI: 10.17648/enipe-2017-60350
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de uma intervenção educativa na qualidade dos registros de enfermagem

Abstract: Objective: to evaluate the impact of an educational intervention on the quality of nursing records.Method: quasi-experimental study with before-and-after design conducted in a hospital. All the nurses in the cardiac intensive care unit of the hospital received the intervention, which consisted of weekly meetings during five months. To collect data, the instrument Quality of Diagnoses, Interventions and Outcomes was applied to the patients' charts in two moments: baseline and after intervention. Results: the ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Studies have revealed improvements in both the detection of patient health problems and the quality of nursing diagnoses (Bruylands et al., 2013; Linch et al., 2017; Patiraki et al., 2017). The training has increased ownership of new ideas and filling in the nursing records (Vabo et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed improvements in both the detection of patient health problems and the quality of nursing diagnoses (Bruylands et al., 2013; Linch et al., 2017; Patiraki et al., 2017). The training has increased ownership of new ideas and filling in the nursing records (Vabo et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Enquanto uma revisão sistemática não mostrou evidências de diferenças mensuráveis entre a documentação eletrônica e em papel sobre os cuidados e enfermagem ou resultados dos pacientes (Urquart et al, 2009), outros estudos demostraram algumas evidências de superioridade da documentação eletrônica (Flemming, Hubner, 2013;Adereti, Olaugun, 2019). (Linch et al, 2017).…”
unclassified